The Effect of Magnitude of Audit Difference and Prior Client Concessions on Negotiations of Proposed Adjustments - Hatfield, Richard C.; Houston, Richard W.; Stefaniak, Chad M.; Usrey, Spencer (The Accounting Review, 2010)
ABSTRACT: This study reports the result of an experiment examining two aspects of the audit context that auditors likely do not suspect can influence audited account balances: the magnitude of an audit difference and the presence of a prior client concession. Negotiation theory shows that negotiators’ initial positions (e.g., clients’ unaudited balances) as well as feelings of reciprocity created by prior negotiations serve to create expectations for the current negotiation and, in turn, affect the outcomes of such negotiations. Our results show that the magnitude of an audit difference involving an estimate (i.e., difference between client’s account balance and the auditor’s independent estimate) as well as the presence of a prior client concession influence auditors’ negotiation expectations. Specifically, auditors proposed smaller adjustments when the magnitude of the audit difference was high and when the client conceded on an audit issue prior to resolving the difference in estimates. These manipulations similarly influence the negotiated outcome, and this influence is fully mediated by the auditor’s initial negotiation position.